Teaching strategies and activities to enhance students' clinical placement in residential aged care facilities: a scoping review. Issue 11 (3rd November 2020) - McCloskey, Rose; Keeping-Burke, Lisa; Donovan, Cindy; Cook, Jessica; Witherspoon, Richelle; Lignos, Nicholas
ABSTRACT: Objective: The purpose of this scoping review was to examine teaching strategies and activities used in nursing students' clinical placement in residential aged care facilities. Introduction: Population aging necessitates that nursing curricula ensure student interest and commitment to working with older adults. While searching for suitable clinical placements that provide students with opportunities to care for older adults, nursing programs have turned to residential aged care facilities. Studies show that carefully planned placement in these environments supports students' needs and offers rich learning possibilities. Inclusion criteria: This review examined intentional teaching strategies and activities used during student placement in residential aged care facilities, and considered research and textual papers on the subject. The strategies and activities included those that took place prior to, during, or after the experience. Methods: The review included qualitative and quantitative research reports as well as text and opinion papers. Only research reports and papers published in English from 1992 to August 2019 were included. The databases searched were: CINAHL (EBSCO), MEDLINE (Ovid), Academic Search Premier (EBSCO), Embase (Elsevier), ERIC (EBSCO), ProQuest Dissertations and Theses, and Google (with advanced search strategies). Two independent reviewers screened citations for inclusion while a third reviewer resolved discrepancies. A table was developed for data extraction to record data relating to the review objective. Specific data extracted included the details on research design, geographical location, year of publication, description of the teaching strategy or activity. Results: Of the 84 research reports and papers that were eligible for full-text review, only 25 (30%) were included in the final set. Sixteen papers were research reports including a variety of qualitative, quantitative, and mixed method designs. The remaining nine were textual papers and included frameworks, descriptions, and evaluations of a teaching strategy or activity. Most research reports and papers identified more than one strategy and/or activity used concurrently. The use of care staff as student mentors and facility orientation for students were the two most common strategies and activities reported. Conclusion: A range of teaching approaches during clinical placements in residential aged care facilities was revealed. These approaches targeted students, staff of aged care facilities, and nursing faculty. Collaborative efforts between aged care facilities and educational institutions allowed for the pooling of resources and the delivery of teaching approaches to students and the engagement of care staff. Many of the approaches were co-designed by educational programs and residential aged care facilities. The number of approaches that used more than one teaching strategy and/or activity reflects an appreciation for the importance of student placements and the complexities of aged care facilities. A lack of longitudinal or evaluative research highlights a gap in the literature. There is a need for further work to understand and evaluate the long-term effects and benefits of teaching strategies and activities used to enhance students' clinical placements in resident aged care facilities.